Flow of the Game: A Hidden Markov Model of Player Engagement in Online Mobile Games - Deng, Jiaying; Lee, Stephanie; Tan, Yong (Information Systems Research, 2025)
Practice- and Policy-Oriented Abstract Mobile gaming is a prominent component of the entertainment industry, yet high attrition rates and low engagement are notorious problems faced by most mobile game publishers. This paper investigates the effects of in-game challenge-related factors and reward ads on player engagement in mobile games. Using a Hidden Markov Model, we analyze how perceived challenge, fluctuation of perceived challenge, and reward ads impact players’ engagement states. Our findings indicate that whereas moderate levels of perceived challenge enhance engagement, excessive challenge level has diminishing returns. Furthermore, fluctuations in perceived challenge help sustain engagement by providing a balance between stimulation and cognitive restoration. Third, reward ads provide access to scaffolds, offering temporary support that helps players move to a higher engagement state, especially during challenging phases of the game. For game developers, incorporating dynamic challenge adjustments can improve player experience and keep players engaged. Additionally, reward ads offer a strategic opportunity for game publishers to monetize their games while maintaining engagement, with a stronger impact when players perceive a higher level of challenge. These insights provide valuable practices for designing mobile games that effectively balance user engagement and monetization strategies, ensuring sustained growth in a competitive landscape.